The Relationship Of Knowledge About The Hazards Of Smoking With Smoking Behavior In The Teenns In Nagori Gajing Jaya Kab. Simalungun In 2021 - Ricard Fredrik Marpaung; Pinondang Hotria Siregar (Institute of Computer Science (IOCS), 2021)
Smoking is a habit that is commonly encountered in everyday life and has become a habit that can provide enjoyment for people who smoke. The purpose of this study was to determine the relationship between knowledge about the dangers of smoking and smoking behavior in adolescents. This type of research is descriptive with a cross sectional approach . The sample of this study consisted of 40 people. Data were analyzed using the chi square test with a significance level of p <α (0.05). The results showed that 21 adolescents (52.5%) had less knowledge about the dangers of smoking, as many as 20 adolescents (50.0%) had smoking behavior including heavy smokers. The probability value (p value) of the relationship between knowledge about the dangers of smoking and smoking behavior is p = 0.008 or p < 0.05 . The conclusion of this study shows that there is a significant relationship between knowledge about the dangers of smoking and smoking behavior in young men in Nagori Gajing Jaya Kab. Simalungun in 2021.